2005
DOI: 10.1113/jphysiol.2005.088948
|View full text |Cite
|
Sign up to set email alerts
|

Cooling blocks rat hippocampal neurotransmission by a presynaptic mechanism: observations using 2‐photon microscopy

Abstract: Over the past decade there has been great interest in the therapeutic potential of brain cooling for epilepsy, stroke, asphyxia and other neurological diseases. However, there is still no consensus regarding the neurophysiological effect(s) of brain cooling. We employed standard physiological techniques and 2-photon microscopy to directly examine the effect of temperature on evoked neurotransmitter release in rat hippocampal slices. We observed a monotonic decline in extracellular synaptic potentials and their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 40 publications
4
37
1
Order By: Relevance
“…In summary, the overall exocytic rate was approximately doubled by increasing temperature from 23°C to 37°C, in good agreement with estimates using cultured hippocampal synapses (Micheva and Smith, 2005), hippocampal slices (Yang et al, 2005), and the calyx of Held (Kushmerick et al, 2006).…”
Section: Synaptic Vesicle Recycling Is Significantly Impeded At Room supporting
confidence: 70%
See 1 more Smart Citation
“…In summary, the overall exocytic rate was approximately doubled by increasing temperature from 23°C to 37°C, in good agreement with estimates using cultured hippocampal synapses (Micheva and Smith, 2005), hippocampal slices (Yang et al, 2005), and the calyx of Held (Kushmerick et al, 2006).…”
Section: Synaptic Vesicle Recycling Is Significantly Impeded At Room supporting
confidence: 70%
“…Several recent studies of murine synapses demonstrated reduced exocytic and recycling rates at room temperature compared with physiological temperature (FernandezAlfonso and Ryan, 2004;Micheva and Smith, 2005;Yang et al, 2005;Kushmerick et al, 2006). We set out to determine whether synaptic vesicle mobility was also affected by temperature using FRAP of FM 1-43-labeled vesicles.…”
Section: Synaptic Vesicle Recycling Is Significantly Impeded At Room mentioning
confidence: 99%
“…Our own recent observations indicate that hypothermia rapidly reduces transmitter release from presynaptic vesicles and suggest that this may be a dominant effect of rapid cooling on central neuronal excitability. 14 The potential clinical utility of cooling for neurological disease has been discussed for half a century. Fay 15 began an extensive investigation of brain cooling in 1938.…”
Section: Cooling and The Brainmentioning
confidence: 99%
“…1,10,13,24,29) A 2-photon microscopy technique demonstrated that a major neurophysiological effect of cooling in the brain is reduction in presynaptic neurotransmitter release. 37) Furthermore, examination of rat hippocampal slices demonstrated that moderate cooling (219 C) induced a reversible block in the network synchrony, which was required to generate EDs, without any blockage of the synaptic transmissions. 15) …”
Section: Antiepileptic Mechanisms Of Focal Brain Coolingmentioning
confidence: 99%